COMMUNICATIVE METHODS AND MOTIVATION OF ENGLISH LEARNING BY ART AND CULTURE STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article says how correctly to motivate students of institute arts and cultures. How to improve their skills in English. The author pay attention on new a way to involve of students from the help blended Learning in English language.